The Effect of Current Ratio, Debt to Equity Ratio, and Return on Assets on Company Value in the Transportation and Logistics Sector Listed on the Indonesia Stock Exchange - Maulana Dzaki Fakhruddin; Sutanti Sutanti (Dinasti Publisher, 2025)
This study aims to analyse the impact of the current ratio, debt to equity ratio, and return on assets on firm value in transportation and logistics sector companies listed on the Indonesia Stock Exchange for the period 2020–2024. This research employs a quantitative approach with secondary data in the form of company financial statements. The sampling technique was carried out using purposive sampling, resulting in 28 companies being selected as the research sample. The data analysis method used is multiple linear regression with panel data, processed using the EViews application. The results of the study indicate that the current ratio has a positive but not significant effect on firm value, the debt-to-equity ratio has a positive and significant effect on firm value, and the return on assets has a positive but not significant effect on firm value. Simultaneously, the current ratio, debt to equity ratio, and return on assets have a significant effect on firm value